2016
DOI: 10.1080/1354750x.2016.1201539
|View full text |Cite
|
Sign up to set email alerts
|

Ratios of leptin to insulin and adiponectin to endothelin are sex-dependently associated with extent of coronary atherosclerosis

Abstract: Leptin to insulin and adiponectin to endothelin ratios are novel derived biomarkers useful for noninvasive diagnostics of initial stages of coronary lesions in patients with coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
(29 reference statements)
0
6
0
6
Order By: Relevance
“… 39 , 40 A previous study also revealed that lipid profiles, including TG, TCH, LDL-C, and HDL-C, have poor predictive values for the severity of coronary diseases due to the influence of drug therapy. 41 Further studies are needed to evaluate the impact of the aforementioned medication on serum leptin concentrations and new MACE development among patients with CAD.…”
Section: Discussionmentioning
confidence: 99%
“… 39 , 40 A previous study also revealed that lipid profiles, including TG, TCH, LDL-C, and HDL-C, have poor predictive values for the severity of coronary diseases due to the influence of drug therapy. 41 Further studies are needed to evaluate the impact of the aforementioned medication on serum leptin concentrations and new MACE development among patients with CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Методом корреляционного анализа были определены ассоциации между различными биохимическими маркерами и степенью поражения коронарных артерий, характеризуемой величиной GS. У мужчин выявлены значимые корреляции между уровнем эндотелина и степенью поражения коронарных артерий (r=0,13; р<0,05), а также между комбинированными маркерами адипонектин/эндотелин (r=-0,16; р<0,05), эндотелин/NOx (r=0,11; р<0,05), адипонектин/эндотелин/NOx (r=-0,15; р<0,05) [38,39].…”
Section: а б г вunclassified
“…Чувствительность теста составила 62,7%, специфичность 70,0% (панель А). У женщин с наличием коронарного атеросклероза (GS >0) ассоциировано сниженное отношение лептин/инсулин <3,5 (p=0,013) с чувствительностью 69,5% и специфичностью 64,5% [38,39]. Обнаруженные гендерные различия в указанных ассоциациях вносят вклад в понимание механизмов атерогенеза у мужчин и женщин [38,39].…”
Section: а б г вunclassified
“…However, the mechanistic connections between these genetic associations and actual symptoms remain to be fully elucidated in a clinically relevant context. Our previous study demonstrated that the balance of circulating levels of adiponectin and endothelin, represented by the adiponectin/endothelin ratio, was associated with coronary stenosis in men (18). Therefore, it was hypothesized that genetic polymorphisms of the ADIPOQ or EDN1 genes may influence the circulating levels of vasoactive mediators and may be associated with the clinical manifestations of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%